THE RELATIONSHIP OF SEAWEED DENSITY WITH MACRO EPIZOOBENTHOS ABUNDANCE IN NIRWANA BEACH PADANG CITY OF WEST SUMATERA PROVINCE - Santi Maya Sari; Zulkifli Zulkifli; Efriyeldi Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTSeaweed community is ecologically refuge, foraging and orphanage for marine life, including macro epizoobenthos. The existence of a food source will affect the density of macro epizoobenthos in the aquatic ecosystem and important its influence on the structure of the food chain in the community of seaweed. This study was conducted in March 2018-April 2018 in Nirwana Beach of Padang City West Sumatra. The aims of research to find out : the density of each type of seaweed, the abundance of a macro epizoobenthos that lives on seaweed community and the relationship between the density of seaweed with a abundance of macro epizoobenthos. Sampling and measurement of water quality was done by using quadratic transect at 3 stations. The results of the study showed that the highest seaweed density has a value 451.4 tegakan/m2 and thehighest macro epizoobenthos abundance has a value 244 ind/m2in the area of seaweed that minimal activity and the lowestseaweedabundance has a value 169 tegakan/m2 and the lowestmacro epizoobenthos abundance has a value 27 ind/m2 in the area of seaweed around the population and settlement activities. The relationship of the density of seaweeds with the macro epizoobenthosdensity very strong i.e. y = 6.371 –0.553x; R² = 0.678; r = 0.82.Keywords: Seaweed Density, Macro Epizobenthos, Abundance, Nirwana Beach